The Bangsamoro cause : reframing insurgent mobilisation and counterinsurgency in the Southern Philippines - Mathew Lauren Bukit (Nanyang Technological University, 2020)
Attempts to frame Muslim armed separatism in the southern Philippines as revolutionary war are undermined by a dominant paradigm of history that obscures the insurgency's character. This orthodoxy impedes effective application of counterinsurgency (COIN) theory because it mischaracterises the incentive structures of mobilisation constituted in the insurgent cause, upon which the Government of the Republic of the Philippines’ COIN strategy is premised. In this paper, Patricio Abinales' orthodoxy critiques are applied to demonstrate how overcoming the misleading account of Muslim armed separatism's history can restore COIN theory’s explanatory value to the insurgency. Stathis Kalyvas' logics of insurgent violence are applied to reframe the insurgents' Bangsamoro cause as exhibiting concurrent supralocal and local logics. Expanding the insurgency's discursive limits to accommodate local agency recasts a more suitable conceptualisation of the Bangsamoro cause, upon which COIN should be premised. There are significant implications for the Bangsamoro Autonomous Region of Muslim Mindanao (BARMM), COIN that reflects the orthodoxy's 'reality.'